VARIASI TЕMРОRAL PERUBAHAN GARIS PANTAI DI SЕKITAR PANTAI KОTA PARIAMAN - Indah Ary Neftya; Fajrin Fajrin; Defwaldi Defwaldi; Ilham Armi (Cross-border, 2023)
Pariaman City has the potential for planning and damage caused by the renovation of the coastline. Shoreline change is one form of change in the coastal area that can occur continuously. The contributing factor to the occurrence of coastline changes can be caused by the presence of arareions and accretion. The aim of this research is to map the change in coastline and to know the pattern of aeration and accretion around Kota Pariaman Beach. This research uses data from Google Earth images over a time span from 2000-2020. Data for the year 2000 was used as a starting point for observing coastline changes (Baseline) and data for 2005-2020 as a Surveyorreline to calculate the rate and distance of Coastline Change using Digital Analysis Software. The results of this research are that from 2000-2020, the number of location points that experienced accretion was 125, while the number of points that experienced abrasion was 64. From 2000-2020, the area around Kota Pariaman Beach experienced a maximum accretion rate of 13,52 m/year in segment 118, while the maximum abrasion rate of -6.12 m/year occurred in segment 182. The maximum accretion distance is located in segment 118 of 265.46 m and the maximum aeration distance occurs in segment 182 of -120.13 m.